Dynamics of the population and dynamics of the memory of an alpine community on the border - Roberta Clara Zanini (Revue de Géographie Alpine)
The aim of this contribution is to correlate the demographic dynamics that can be observed in the Alps area, with those of management, transmission and valorisation of the local historical memory; in particular, this work focuses on the Piedmont town of Macugnaga, where an ethnographic research was conducted. Moving from the main theoretical, demographic and geographic proposals that concern the phenomena of repopulation of the alpine area, and from anthropological reflections on the subject of memory, there arose the need for a dialogue between the two perspectives and to adopt a multi-level method that would integrate the macro approach of demographic reconstructions with the “ground level” approach of ethnography. The increasing number of new inhabitants in the Alps raises the question of who could legitimately call themselves “mountain dwellers” and how these dynamics of belonging manifest themselves. One of the most significant ways in which belonging to the community is expressed, is through the participation in the management and transmission of the local historical memory. It will be shown how in this case study, the history of the community, characterised by early immigration movements, gave rise to the coexistence of different transmissible memories that concern different aspects of the local history. In addition, the current composition of the population is characterised by the simultaneous presence of people who express different and varied ways of living in the mountains.